Effectiveness of Islamic symbols in TV advertisements in reaching organizational clients - Ali, Azhani (2015)
This research was conducted to examine the impact of Islamic symbols used in television (TV) advertisements in influencing consumer’s attitude, trust, involvement and purchase intention. The general objective of this research is to determine the effectiveness of Islamic symbols in TV advertisements in reaching organizational clients. Specifically, this study aims i) to determine the effectiveness of Islamic symbols used in TV advertisements in influencing attitude towards the TV advertisement, ii) to determine the strength of Islamic symbols used in TV advertisements in influencing trust towards the TV advertisement, iii) to determine the strength of Islamic symbols used in TV advertisements in influencing involvement towards the TV advertisement, and iv) to determine the effectiveness of Islamic symbols used in TV advertisements towards influencing purchase intention of products advertised. The framework for this study was constructed based on the Elaboration Likelihood Model (ELM) which suggested that, persuasive messages were processed through two routes; the central route and the peripheral route, which differ, based on consumer’s level of involvement. ELM explained that individuals with high involvement level would elaborate the information via central route, whilst, those who used the peripheral routes were those with low level of involvement. Advertisers were suggested to use the appropriate cues to help consumers process the information. The research has utilized the experimental approach. Two experiments were conducted for this research whereby, the first experiment involved 23 graduate students who registered in the Integrated Marketing Communication course and the second experiment involved 50 undergraduate students who registered in Public Speaking course, offered by the Faculty of Modern Languages and Communication (FBMK), Universiti Putra Malaysia (UPM). There were two stages involved in this study, namely, the pre-test and the post-test stages. The former was conducted to identify the changes that occurred before the respondents were exposed to the TV advertisement with the Islamic symbols whilst the latter was conducted to identify the changes that occurred after the respondents were exposed to the TV advertisements. During the pre test, the respondents were exposed to four advertisements without the presence of Islamic symbols, whereas, for the post-test, respondents were exposed to another 4 advertisements which had Islamic symbols. Data on the respondents’ attitude, trust,involvement and purchase intention were collected using two sets of questionnaires (pre-test and post-test). For the first experiment, the result showed that there was insignificant change in respondents’ attitude, trust, involvement and purchase intention before and after they had been exposed to Colgate, Sunsilk and McDonald Samurai burger advertisements with the implementation of Islamic Symbols. But, there was a significant change in respondents’ attitude after watching HSBC Amanah advertisement. However, the changes on trust, involvement and purchase intention tested using the same advertisements were reported as insignificant. The result on the second experiment was almost similar, whereby the result showed insignificant change in respondents’ attitude,trust, involvement and purchase intention towards all advertisements used in this research. Based on the overall observation of the experiment towards the advertisement and the result of the experiment, it shows that the effectiveness of Islamic symbols used in our current TV advertisements was not strong enough to affect consumers’ attitude,trust, and involvement and purchase intention. The change on respondent’s attitude towards HSBC Amanah advertisement in the first experiment was more likely to be influenced by emotional dimensions highlighted in the storyline. The findings suggest that the implementation of Islamic symbols in TV advertisements need to be more prominent. Previous researches gave indications that the use of Islamic symbols in advertisements may affect the consumers, but the current TV advertisements with the implementation of Islamic symbols shown in Malaysia are not strong and effective enough due to certain elements such as the size of the symbols, the duration of the symbols being exposed during the advertisements. Therefore, it is suggested that in future, the use of Islamic symbols in advertisements should be more bold and meaningful in order to attract consumers’ attention.